Optimal control and cost-effectiveness analysis for bacterial meningitis disease - Belay, Malede Atnaw; Abonyo, Jeconia Okelo; Alemneh, Haileyesus Tessema; Engida, Habtamu Ayalew; Ferede, Melkamu Molla; Delnessaw, Samuel Abebe (Frontiers in Applied Mathematics and Statistics, 2024)
In this study, we developed an optimal control deterministic model for the dynamics of bacterial meningitis disease. The objective was to investigate the efficiency and cost-effectiveness of the three controls (prevention, treatment, and screening) in curtailing the spread of bacterial meningitis. To accomplish this, we applied Pontryagin's maximum principle to derive the optimality system. We examined different combination strategies to investigate the effect of the interventions on the spread of bacterial meningitis. We used an incremental cost-effectiveness ratio (ICER) to examine which control technique was the most successful. The simulation results show that combining prevention and screening is the most cost-effective strategy. The objective function and the incremental cost-effectiveness ratio further support this result, indicating that maximum utilization of prevention and screening is required for the entire period.